Estrogenic activities of di-2-ethylhexyl phthalate - Jin, Qiumei; Sun, Zengrong; Li, Yan (Frontiers of medicine, 2008)
Phthalate esters are widespread in the environment. They have been described as being one of the most abundant man-made environmental contaminants that may be adverse to human health. Particularly, di-2-ethylhexyl phthalate (DEHP) has been shown to cause reproductive and developmental toxicity and is suspected to be an endocrine disruptor. The primary objective of this study is to determine the estrogenic activity of DEHP. Estrogenic activities of DEHP were studied by in vitro assays of human breast cancer MCF-7 cell proliferation. Estrogen-dependent MCF-7 cells were grown in RPMI1640 medium containing 10% fetal bovine serum. Five days before the addition of the test compounds, the cells were washed by phosphate balanced solution (PBS), and the medium was substituted with a phenol red-free RPMI1640 medium containing 5% dextral charcoalstripped Fetal Bovine Serum (FBS). Fresh medium was added to the respective test compounds and the control cell received only the vehicle (ethanol). The proliferation of MCF-7 cell was analyzed by the MTT assay, growth curves, mitotic index and colony forming efficiency. Compared with the ethanol control cells, the proliferation of tested cells treated with DEHP, like estradiol, was significantly enhanced and the activity of the cell proliferation reached the maximum at 1 × 10 −3 mol/L DEHP. The relative proliferative potency of DEHP was 0.000 001 with a relative proliferative effect of 97.32%. During the log phase, the mitotic index of the tested cells treated with DEHP and estradiol was significantly increased. The cell cloning efficiency was enhanced, which was treated by 10 −3 mol/L DEHP only for 48 hours. The results show a time-dependent and dose-dependent model. Di-2-ethylhexyl phthalate enhanced the proliferation of human breast cancer MCF-7 cells in vitro and might demonstrate an estrogenic activity.